Early Cretaceous palynostratigraphy of the Abu Tunis 1x borehole, northern Western Desert, Egypt, with emphasis on the possible palaeoclimatic effect upon the range of Dicheiropollis etruscus in North Africa. (2nd January 2016) - Deaf, Amr S.; Harding, Ian C.; Marshall, John E.A.
Abstract : Recent hydrocarbon exploration in the northern sector of the Western Desert in Egypt has revealed relatively rich hydrocarbon accumulations, mainly of gas, and demonstrate promising future prospects. In order to improve our understanding of this area and to provide a biostratigraphical framework for the hitherto poorly dated Lower Cretaceous successions, a palynological analysis was carried out on 57 ditch cutting samples from the Abu Tunis 1x borehole. Palynostratigraphic investigation on these samples has enabled the identification of three new palynostratigraphically defined age divisions with three corresponding palynozones defined by first uphole occurrences of gymnosperm and angiosperm pollen and dinoflagellate cysts. Spore and pollen grains recovered from the Abu Tunis 1x borehole show the characteristics of the pre-Albian Dicheiropollis / Afropollis Phytogeographical Province. Discrepancies in the reported range of Dicheiropollis etruscus, when compared with earlier (Berriasian) appearances in West Africa and later (late Hauterivian) appearances in East Africa, may be attributed to palaeoecological factors. Dicheiropollis etruscus is accepted as having a cheirolepidiacean conifer affinity and is regarded as having been produced by a thermophilous plant. Here, we suggest that Dicheiropollis etruscus was adapted to arid conditions. Dicheiropollis etruscus thus first appeared in hot, dry palaeo-subtropical African regions, but as Western Gondwana broke up and the African Plate moved northeast during/after the Late Jurassic, the region that is now present-day Egypt, Libya and Sudan had moved by the late Hauterivian into a subtropical position; the ensuing increased aridity thus allowed Dicheiropollis etruscus to migrate into these areas.